2248. Changes in Lipid Profiles for Patients to Tenofovir Alafenamide (TAF)-Containing Regimens: Perspectives from a Military HIV-Positive Cohort. (26th November 2018) - Ewers, Evan; Won, Seunghyun; Okulicz, Jason; Ferguson, Tomas; Deiss, Robert; Maves, Ryan; Kronmann, Karl; Lalani, Tahaniyat; Agan, Brian; Whitman, Timothy J; Ganesan, Anuradha
Abstract: Background: Tenofovir alafenamide (TAF) was approved in 2015 for use in HIV-1. TAF decreases risk of renal and bone toxicity compared with tenofovir disproxil fumarate (TDF). Early clinical trials reported median increases in low-density lipoprotein (LDL) of 20–29 and 9–13 mg/dL for total cholesterol (TC) following switch therapy from TDF-containing regimens at 48 weeks, raising concern for increased cardiovascular (CVD) risk over time. We assessed real-world changes in serum lipid concentrations following transition to TAF-containing regimens. Methods: Eligible subjects in the U.S. Military Natural History Study, a longitudinal cohort of HIV-infected military beneficiaries, had been switched from TDF to TAF-based regimens, and had pre- and post-switch lipid profiles available. Antiretroviral therapy history, serum lipids, CD4 count and viral load were collected from the study database. Wilcoxon rank-sum test was used to compare lipid profile changes. Results: As of January 1, 2018, 408 subjects on TDF switched to TAF; 238 had pre and post lipid profiles. Subjects were primarily male (95%), 45.4% African American, 70% were ≥40 years old at TAF start; 8% had CVD and 10% had diabetes. Changes in lipid profiles and CD4 count are presented in Table 1. No difference was seen when categorized by gender, race, or age. Lipid changes were not seen in subjects switched from an efavirenz (EFV) regimen. Increases in TC, HDL, and LDL were observed in those switched from rilpivirine (RPV) ( P = 0.002, P = 0.0404, and P = 0.0296) or elvitegravir (EVG) ( P < 0.0001, P = 0.0003, P = 0.0040) regimens. Conclusion: We found significant changes in serum lipids, albeit lower than median changes observed in licensing trials. Changes were not observed in those switching from EFV, contrasting with those switching from RPV or EVG. Disclosures: All authors: No reported disclosures.